Perceived Augmentation of Augmented Reality Features on Affective Response, Cognitive Response, and Purchase Intention: A Systematic Literature Review in the Context of Skincare Product on E-Commerce Platform - Insaniyah, Syarifatul; Arifah, Ika Diyah Candra (Journal of Digital Business and Innovation Management, 2025)
This study explores how perceived augmentation of Augmented Reality (AR) features influences affective response, cognitive response, and purchase intention, with a specific focus on Somethinc products on e-commerce platforms. Utilizing a Systematic Literature Review (SLR) approach, Python-based bibliometric tools were employed to retrieve, clean, and analyze academic publications from databases such as Scopus, ScienceDirect, and IEEE Xplore. A total of 518 articles were initially identified using targeted keywords, and 58 met the inclusion criteria. Findings reveal consistent support for AR as a persuasive tool that enhances emotional engagement, mental processing, and ultimately drives purchase decisions—especially in the beauty and skincare industry. This review provides a foundation for future empirical research and offers theoretical and managerial implications in the domain of AR-driven social commerce.